“De volta ao sonho”: a jornada da graduação em Medicina - Trevisan, Caio Vinícius Ribeiro (Universidade Federal de São Carlos, 2025)
A reflective narrative about a unique academic journey marked by the integration of prior knowledge from school during medical school, facing challenges such as a suspension of enrollment, the COVID-19 pandemic, and the struggle with depression during her six years of undergraduate studies. Upon entering medical school with a constructivist methodology, she needed to integrate her prior knowledge and use adverse experiences as catalysts for her personal and professional growth. The constructivist approach to medicine led to effective learning and guided her toward a patient-centered practice, recognizing the importance of individuality and fostering empathy and respect in clinical relationships. Completing this training not Only provides her with a medical degree, but also ethical and compassionate medical practice. A journey that reflects the ability to transform challenges into driving forces for building a unique medical education.
“Back to the dream: the journey of medical degree
Keywords: Metodologia ativa; Narrativa Reflexiva; Medicina; CIENCIAS DA SAUDE::MEDICINA